Psychological dimensions in alcohol use disorder: comparing active drinkers and abstinent patients - Zizzi, Alessio; Berri, Isabel Margherita; Berri, Alessandro; Occhipinti, Martina; Escelsior, Andrea; Guglielmo, Riccardo; Pereira Da Silva, Beatriz; Amore, Mario; Serafini, Gianluca (Frontiers in Psychiatry, 2024)
Background: Alcohol misuse use disorder (AUD) is a major public health concern due to its various physical, psychological, and social consequences. Despite regulatory differences, abstinence remains the primary treatment objective. Addressing the multifaceted nature of alcohol use disorder requires a comprehensive approach.Methods: 150 AUD patients (66%male) with a mean age of 54.10±11.3 years were recruited for the study. Depression, impulsivity, alexithymia, and hopelessness were assessed to determine if there were significant differences in these dimensions between abstinent (N=72) and active drinkers (N=78).The study found significant differences in the psychological dimensions scores, active drinkers exhibited higher levels of depression, impulsivity, alexithymia, and hopelessness compared to abstinent patients.Treatment outcomes for patients with AUD vary between regulatory agencies, but abstinence remains the safest and most preferred objective in managing AUD. Prioritizing abstinenceoriented interventions is crucial for achieving long term recovery and minimizing relapse risk. These results emphasize the intricate relationship between alcohol misuseAUD and mental health issues, highlighting the need for comprehensive interventions addressing both alcohol consumption and associated psychological distress. Promoting abstinence (or at least reducing alcohol consumption) not only preserves mental health but also prevents life-threatening consequences such as suicide.